The Disenchantment of the Wonderful - A Doll’s House and the Idealist Imagination - Kallenbach, Ulla (Nordic Theatre Studies, 2014)
During the course of the nineteenth century, the notion of imagination under- went a radical redefinition. From being the highest, divine, power of man to being subjected to a growing pathologization and degradation, the redefinition of imagination played a central role in the transition from idealism and roman- ticism to the emerging modernism and realism. Henrik Ibsen’s A Doll’s House (1879) may be read into this particular context with its ‘disenchantment’ of the ‘wonderful’ – a word which Georg Brandes termed the very keyword of romanticism. Focusing on the specific Scandinavian context, where idealist aesthetics continued to be particularly strong, I will examine A Doll’s House from the perspective of the contemporary spectator in the context of an on-going Nordic aesthetic dispute. The contemporary Scandinavian reviews will serve to bear evidence of this dispute. In the article, I analyse how the play thematizes imagination and employs recurrent references to idealist culture in order to disenchant the romantic imagination of the wonderful. The analysis will focus in particular on the representation of the characters of Nora and Helmer, but also comes to implicate the spectator of the play.